Modelling of Intelligent Multi-Agent based E-health Care System for People with Movement Disabilities - Bielskis, A. A.; Denisovas, V.; Drungilas, D.; Gricius, G.; Ramašauskas, O. (Elektronika ir Elektrotechnika, 2008)
An approach is proposed in creating of an intelligent e-health care environment by modelling of an adaptive multi-agent-based ehealth and e-social care system for people with movement disabilities. Human’s Arousal Recognition Module (HARM) described based on online recognition of human’s ECG, EDA and body temperature signals by using embedded Atmega32 type microcontrollers. Multiagent based online motion control of multiple wheelchair-type robots is realized based on integration of an adaptive Fuzzy Neural Network Control algorithm into ATmega32 microcontroller. Human Computer Interaction in the system is realized in providing of necessary e-health care support actions for users with some movement disabilities by using Java–based JACK agent oriented environment. The dynamic multi-agent system is proposed to permanently realizing e-social care support actions for disabled by gathering data such as current position of robot and user‘s state information; finding decisions for given situation; sending signals to performing appropriate actions of the objects in the system. Ill. 6, bibl. 5 (in English; summaries in English, Russian and Lithuanian).